Das Tagebuch von Leo Thun-Hohenstein (1825-1842) Einblicke in die Jugendjahre des späteren Ministers für Cultus und Unterricht - Prokosch, Michael (2023)
The edition of Leo Thun-Hohenstein's diary allows an intimate look at the early years of the later reformer of Austrians education system. Dealing with foreign cultures and questioning social norms characterized Thun's adventurous youth as a high aristocrat and allowed him to grow into a socially committed politician who, after the revolutions of 1848, was to help determine the fate of the Habsburg Empire. A biography of Thun and a source-critical analysis provide additional information on the environment of this fascinating personality.